Replication data for \"Impact of Timanian thrust systems on the late Neoproterozoic–Phanerozoic tectonic evolution of the Barents Sea and Svalbard\" - Koehl, Jean-Baptiste P. (DataverseNO, 2021)
High-resolution versions of the figures of the Koehl et al. (2021; \"Impact of Timanian thrust systems on the late Neoproterozoic–Phanerozoic tectonic evolution of the Barents Sea and Svalbard\") submitted for review.